Emerging Trends of Capital Market and Mutual Fund in India - Kumar Purbey, Dr. Uttam (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
Mutual fund is a trust that pools money from a group of investors and invest the money which collected into asset classes that match the stated investment objectives of the scheme. Since the stated investment objective of a mutual fund scheme generally forms the basis for an investor's decision to contribute money to the pool, a mutual fund can not deviate from its stated objectives at any point of time. Every Mutual Fund is managed by a fund manager, who using his investment management skills and necessary research works ensures much better return than what an investor can manage on his own. The capital appreciation and other incomes earned from these investments are passed on to the investors in proportion of the number of units they own. When an investor subscribes for the units of a mutual fund, he becomes part owner of the assets of the fund in the same proportion as his contribution amount put up with the corpus. Mutual Fund investor is also known as a mutual fund shareholder or a unit holder. Keyword: - Mutual Fund, Capital, Shareholder, Investor, Money.